Role of Renal Biopsy in Managing Paediatric Renal Disease in a Tertiary Care Setting - Yadav, Shankar Prasad; Thakur, Jitendra (Journal of Nepal Paediatric Society, 2021)
Introduction: The contribution of renal biopsy is of major importance in many paediatrics renal diseases. This prospective study analysed the clinic-pathological spectrum of the biopsied cases, complications related to renal biopsy and its effect on management.Methods: USG guided percutaneous renal biopsy was performed in indicated children. Laboratory findings, complications of the procedure, histological diagnosis and its effect on management were obtained from all patients who underwent renal biopsy from April 2019 to March 2020. The data were finally analysed using descriptive statistics.Results: Total 50 cases were enrolled during the study period. There were 24 males and 26 females with age range from two to 16 years. The common indications for biopsy were acute nephritic syndrome (25 cases), including both primary glomerulonephritis (11 cases) and secondary glomerulonephritis (14 cases), of which lupus nephritis contributed (11/25) cases, followed by atypical/ steroid resistant or dependent nephrotic syndrome (18 cases). Among primary glomerulonephritis, diffuse proliferative glomerulonephritis was most common pathological finding (11/25). One had crescentric glomerulonephritis. Lupus nephritis predominantly had Class IV/V pathology (6/11). Of 18 nephrotic syndrome cases, nine had minimal-change-disease and five had focal-segmental-glomerulosclerosis. The complications associated with procedure were self-resolving gross hematuria in eight cases, perirenal hematoma requiring plasma transfusion in one case. Adequate renal tissue sample was obtained in 47 of the renal biopsies. Three cases underwent repeat biopsy. Immunosuppressive therapy was altered as per the biopsy report among 18 cases.Conclusions: Our study showed that renal biopsy is a safe, reliable and effective technique in children. It resolutes many diagnostic dilemma and helps in effective management.